Pedagogy at university in transition: reflections from the Bologna Process and the voices of pedagogical managers in Engineering courses in Portugal - M. T. Stano, Rita de Cássia; Vieira, Flávia (Revista Diálogo Educacional, 2014)
The present paper discusses the role of Pedagogy and the promotion of teaching quality at university within current reform policies in higher education resulting from the Bologna Process. These policies have also influenced public policies in Brazil and theoretical-methodological elements are presented which may support a future study in that context. In order to understand the impact the Bologna Process upon innovation and the supervision of teaching practice, an exploratory study was conducted in Portugal based on interviews to six pedagogical managers of Engineering courses from three public universities. Innovation and supervision seem to operate in a transitional territory, incorporaring conflitual logics which somehow result from tensions inherent to current changes. However, signs of a more reflective and collective pedagogical culture were found, which may foster the reshaping of the teching profession in the academic setting.